Autonomous Management of Educational Units At Al-Islamiyah Education and Social Foundation (Yapisa) Tanggulangin District, Sidoarjo Regency - Solichan Solichan; Istikomah Istikomah; Akhtim Wahyuni (Proceedings of The ICECRS, 2020)
The National Education System Law No. 20 of 2003 as a refinement and replacement of Law No. 2 of 1989 strengthens the implementation of education decentralization, which was originally top down to bottom up, with the hope of improving the quality of education. Including the granting of autonomy in the management of educational units in foundations will provide broader opportunities for educational unit managers to find competitive strategies in the competitive era of achieving strong and independent educational outputs. This study aims to determine the extent of autonomy in the management of educational units in Al-Islamiyah educational and social foundations (yapisa). In this case the authors use qualitative phenomenological research methods, and historical methods. The data collection technique uses participatory observation, interviews and document review, while the data analysis uses descriptive. The results of this study, that the Foundation is very free in giving full autonomy to each education unit under its auspices. Most foundations develop their educational institutions, but educational institutions in Yapisa actually develop foundations.